Methylated chalcones are required for rhizobial nod gene induction in the Medicago truncatula rhizosphere - Wu, W; Zhuang, Y; Chen, D; Ruan, Y; Li, F; Jackson, K; Liu, C-W; East, A; Wen, J; Tatsis, E; Poole, PS; Xu, P; et al. (Wiley, 2024)
Legume nodulation requires the detection of flavonoids in the rhizosphere by rhizobia to activate their production of Nod factor countersignals. Here we investigated the flavonoids involved in nodulation of Medicago truncatula. We biochemically characterized five flavonoid-O-methyltransferases (OMTs) and a lux-based nod gene reporter was used to investigate the response of Sinorhizobium medicae NodD1 to various flavonoids. We found that chalcone-OMT 1 (ChOMT1) and ChOMT3, but not OMT2, 4, and 5, were able to produce 4,4'-dihydroxy-2'-methoxychalcone (DHMC). The bioreporter responded most strongly to DHMC, while isoflavones important for nodulation of soybean (Glycine max) showed no activity. Mutant analysis revealed that loss of ChOMT1 strongly reduced DHMC levels. Furthermore, chomt1 and omt2 showed strongly reduced bioreporter luminescence in their rhizospheres. In addition, loss of both ChOMT1 and ChOMT3 reduced nodulation, and this phenotype was strengthened by the further loss of OMT2. We conclude that: the loss of ChOMT1 greatly reduces root DHMC levels; ChOMT1 or OMT2 are important for nod gene activation in the rhizosphere; and ChOMT1/3 and OMT2 promote nodulation. Our findings suggest a degree of exclusivity in the flavonoids used for nodulation in M. truncatula compared to soybean, supporting a role for flavonoids in rhizobial host range.